Precarious Employment and Fathering Among Men in Higher Education Institutions - Modubi, Ngoakwana Nkakga (Department of Psychology, 2022)
There has been an increase in literature involving female academic staff on precarious employment contracts and how they balance their work and family lives. However, research involving male academic staff on insecure contracts with children is limited, particularly within the South African context. My thesis addressed this gap by exploring how precariously employed men in higher education institutions in Cape Town understand the concepts of fatherhood, their own practices of fathering, and what influence their employment has on their involvement with their children. Given that precarious employment in higher education institutions is a salient problem in South Africa, this study investigated the ways in which such employment conditions in higher education shape fathering practices. This study was informed by a broader study, which aimed to understand (a) how men in precarious employment in the formal and informal employment sectors define fatherhood, (b) what practices they associate with fathering, and (c) how, if at all, their employment conditions shape their fathering practices. I conducted a qualitative research study using purposive and snowball sampling methods to procure a sample of seven men aged 34 to 57 years old. Data was collected through individual, semi-structured interviews. I used Interpretive Phenomenological Analysis to understand the fathers' experiences. Findings from the study show that fatherhood is constructed through the participants' ability to provide for their families and be responsible role models to their children. Having a good relationship with their children is important for the men, and they establish these relationships by spending time with their children. The findings also show that participants perceived HEIs as exploitative, relying on PhD students who are in the process of establishing their academic careers for teaching purposes. The income received by the men on these non-permanent contracts is not sufficient for them to provide for themselves and their families, and they therefore work multiple jobs so that they can receive a better income. The fathers' experiences also show that precarious employment conditions in higher education institutions enable some fathers to be involved in their children's care due to flexibility in their working hours. However, for some of the men, father and child co-residence was prohibited by migration, resulting in reduced contact with their children.